2007
DOI: 10.1111/j.1365-2753.2006.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient factors associated with attrition from a self‐management education programme

Abstract: Objective To examine utilization patterns of diabetes self-management training (DSME) and identify patient factors associated with attrition from these services at an ambulatory diabetes education centre (DEC). Methods A retrospective medical chart review of first time visits (536) to the centre between I August 2000 and 31 July 2001 was conducted for patients with type 2 diabetes. Descriptive analyses were conducted to examine utilization patterns over a I-year period. Multivariable logistic regression was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 48 publications
0
17
1
Order By: Relevance
“…This preference may be especially true for employed individuals, who, in our study, had a lower mean number of contacts compared with those who were unemployed. Similarly, previous studies also reported higher attrition rates in DSME programmes among employed compared with unemployed or retired individuals with diabetes [21,22].…”
Section: Discussionmentioning
confidence: 64%
“…This preference may be especially true for employed individuals, who, in our study, had a lower mean number of contacts compared with those who were unemployed. Similarly, previous studies also reported higher attrition rates in DSME programmes among employed compared with unemployed or retired individuals with diabetes [21,22].…”
Section: Discussionmentioning
confidence: 64%
“…Lower-thanexpected attendance rates were often reported. 10 In alternative modalities that efficiently reach a majority of the community-dwelling diabetes clients, DMSE is warranted. 6 Studies examining computer-assisted learning (CAL) as an adjunct to conventional DSME have been increasing in recent years.…”
mentioning
confidence: 99%
“…Previous studies have shown higher attrition rates in diabetes self-management education classes for the employed compared with the unemployed or retired (13,14). Employment demands may be qualitatively different from caregiving demands, and less accommodating to the requirements of diabetes care.…”
Section: Discussionmentioning
confidence: 96%